Critical appraisals about the foundation of duties of protection in the Peruvian legal system - Moreno More, César E. (2014)
The acceptance of the theory of the duties of protection isstrongly conditioned by systemic features of each legal order. if the premise and the scope of the doctrine are overlooked, and its historical and dogmatic location is dissociated from it, eventually it will be created a wasteful duplication of compensatory systems, in a legal order where the same result is obtained using the tort law. Nevertheless, it does not mean that creditor’s person or property will not be relevant with respect to contractual relationship. it is enough just to understand that this will only happen in a few situations in which the possibility to affect the rights of obligee falls within the specific contractual obligation. Out of these situations, any effort to turn tort damage into contractual damage will nothave otherwise forced and unsustainable consequences.